2023
DOI: 10.3390/nu15102331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant-Based Diets on Anthropometric and Cardiometabolic Markers in Adults: An Umbrella Review

Han Shi Jocelyn Chew,
Felicia Kai Xin Heng,
Si Ai Tien
et al.

Abstract: We conducted an umbrella review to consolidate the evidence of adopting plant-based diets on anthropometric and cardiometabolic outcomes. Six electronic databases (CINAHL, EMBASE, PubMed, Scopus, the Cochrane Library, and Web of Science) were searched for systematic reviews with meta-analysis (SRMAs) published from each journal’s inception until 1 October 2022. Effect sizes from SRMAs and primary studies were pooled separately using random effects models. Overlapping primary studies were removed for primary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“… 1 , 7 Already at the late-stages of urbanisation, high-income countries reap the benefits of decades-long established health education, health care, nutrition, and accessibility to healthy foods, with promising reductions across all CV risk factors. 31 , 32 , 33 , 34 Yet, high-income countries are anticipated to suffer from worsening overall CV mortality despite the gains in CVD prevention, suggesting the unique challenges they will face in the future, with the improvement in CVD prevention offset by increased longevity and ageing populations. Apart from contributing to the increasing CV mortality, the economic implications of top-heavy age structures will include a shrinking working-age population that can affect economic productivity and competitiveness; whilst bearing a growing burden of healthcare expenditure for the rapidly ageing populations.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 7 Already at the late-stages of urbanisation, high-income countries reap the benefits of decades-long established health education, health care, nutrition, and accessibility to healthy foods, with promising reductions across all CV risk factors. 31 , 32 , 33 , 34 Yet, high-income countries are anticipated to suffer from worsening overall CV mortality despite the gains in CVD prevention, suggesting the unique challenges they will face in the future, with the improvement in CVD prevention offset by increased longevity and ageing populations. Apart from contributing to the increasing CV mortality, the economic implications of top-heavy age structures will include a shrinking working-age population that can affect economic productivity and competitiveness; whilst bearing a growing burden of healthcare expenditure for the rapidly ageing populations.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between diet and CV health is well established, making dietary interventions a crucial component of preventative and therapeutic strategies [ 18 , 19 , 20 , 21 , 22 ]. Several dietary patterns, such as plant-based diets, the Mediterranean diet, and the Nordic dietary pattern, have been found to be effective in reducing the risk of CVDs [ 2 , 23 , 24 , 25 , 26 , 27 , 28 ]. The common characteristics of these nutritional patterns are the consumption of whole-food groups, reduced or eliminated animal food intake, and increased consumption of plant-based foods.…”
Section: Introductionmentioning
confidence: 99%
“…Umbrella reviews of existing systematic reviews and/or meta-analyses, called overviews in the Cochrane Handbook, use systematic reviews (SRs) methodology on existing SRs or meta-analyses [15]. Other umbrella reviews in the existing body of research on this topic are available, comparing vegetarian and omnivorous diets and various health outcomes [16][17][18]. In the study of Oussalah et al [17], compared to omnivorous diets, vegetarian diets showed lower blood cholesterol levels and a reduced risk of adverse health outcomes, including diabetes, heart disease, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present umbrella review, we have focused on cardiovascular disease. Another umbrella review found that plant-based diets had significant effects on anthropometric parameters (e.g., body weight, BMI, waist circumference), but not cardiometabolic markers (e.g., diastolic blood pressure, HDL-C, triglyceride, LDL-C, and fasting blood glucose) in adults with Western eating habits [18]. Dinu et al [16] summarized and evaluated the effects of different diets (e.g., low-carbohydrate, high-protein, low-fat, paleolithic, low-glycemic-index/load, intermittent energy restriction, Mediterranean, Nordic, vegetarian, Dietary Approaches to Stop Hypertension (DASH), and portfolio dietary pattern) on anthropometric parameters and cardiometabolic risk factors.…”
Section: Introductionmentioning
confidence: 99%